Regulation of conformation and activity of nuclear NF-kappaBeta p65 by phosphorylation, chaperones and p65 DNA-binding - Milanovic, Maja; Justus Liebig University Giessen (My University, 2014)
The TF NF-kB is an important regulator of immunity, stress responses as well as apoptosis, cell cycle progression and oncogenesis. NF-kB is activated by various stimuli and regulates expression many different target genes. The first part of this work shows that stimulation of cells with the cytokines TNF or IL-1 results in a profound conformational switch of the NF-kB subunit p65, as revealed by limited proteolysis assays. The cytokine-triggered reconfiguration of p65 mainly occurs for p65 contained in the nuclear fraction. Immunoprecipitation experiments with various p65-specific antibodies identified a conformation-specific monoclonal antibody that preferentially immunoprecipitates the inducibly refolded p65 protein. Cytokine inducible structural changes of p65 are mainly mediated by posttranslational p65 modifications. Mutations of individual p65 phosphorylation sites cause structural changes in p65 and thus control subsequent ubiquitination and association with transcriptional cofactors such as CBP/p300 and MYBBP1a. These experiments suggest that phosphorylation-induced conformation changes contribute to an alternative p65 configuration and thus to the specification of the NF-kB response. As chaperones are frequently found to be important for proper folding of proteins, the constitutive and inducible association of chaperones Hsc/Hsp70 and Hsp90 with p65 was tested. Coimmunoprecipitation experiments revealed constitutive interaction between p65 and Hsp70. Limited proteolysis assays showed that constitutively bound chaperones of the Hsc/Hsp70 family were not important for the cytokine-induced conformational switch per se, but rather control the fidelity of protein rearrangement. Accordingly, pharmacologic inhibition of Hsp/Hsc70 revealed that these chaperones also control the level of p65 modifications and regulate TNF-triggered ubiquitination and degradation of p65. A specific Hsc/Hsp70 inhibitor significantly reduced p65-triggered reporter gene activity, showing that chaperone-activity provides an important contribution for p65-induced transcription. It is thus likely that inducible conformational changes of p65 increase the intramolecular flexibility and thereby expand and specify the repertoire of possible modifications and protein-protein interactions. The cytokine-induced conformation switch is independent from the DNA-binding ability of p65, as shown by the analysis of p65-/- MEFs that were reconstituted with a p65 DNA-binding mutant. The DNA-binding mutant and a further p65 mutant additionally mutated in the NLS were used for the second part of this work. Reconstituted knockout cells were used to investigate the contribution of p65 DNA-binding for the induction of TNF-induced and p65-dependent transcription of NF-kB target genes. Analysis of relative mRNA expression by qRT-PCR identified a set of genes which were as expected fully dependent on p65 DNA-binding. These experiments also showed that another group of genes which is independent of direct binding of p65 to its target kB sites, implicating the importance of p65 protein-protein interactions for its ability to trigger transcription. These differentially reconstituted cells will be useful in the future to identify p65-dependent non-genomic functions of NF-kB.

Der Transkriptionsfaktor NF-kB ist bei der Regulation der Stressantwort, der Apoptose und angeborenen Immunität beteiligt. Daher wird NF-kB durch unterschiedlichste Signale aktiviert und induziert die Expression von vielen verschiedenen Genen. Der erste Teil dieser Arbeit zeigt mit Hilfe von "limited proteolysis" Experimenten, dass die Stimulation von Zellen durch die Zytokine IL-1 oder TNF in einer Konformationsänderung des NF-kB p65 Proteins resultiert. Die Zytokin-induzierte Konformationsänderung des p65 Proteins war nur für das im Zellkern befindliche p65 Protein zu beobachten. Immunopräzipitationsexperimente erlaubten die Identifizierung eines Konformations-spezifischen p65 Antikörpers der präferentiell das umgefaltete p65 Protein erkennt. Die Zytokin-induzierten Strukturänderungen werden primär durch Phosphorylierungsereignisse am NF-kB p65 Protein induziert. Mutationen in einzelnen p65 Phosphorylierungsstellen resultierten in Strukturänderungen und kontrollierten auch weitere Eigenschaften des p65 Proteins wie beispielsweise die Ubiquitinierung und die Assoziation mit transkriptionellen Kofaktoren wie CBP/p300 und MYBBP1a. Auch die Induktion der p65 Phosphorylierung durch Behandlung der Zellen mit dem Phosphatase-Inhibitor Calyculin A führte zu einer induzierten Strukturänderung. Da Chaperone häufig an der Regulation der Proteinfaltung beteiligt sind, wurde die Interaktion von p65 mit Hsp Proteinen untersucht. "Limited proteolysis" Experimente zeigten, dass konstitutiv gebundene Hsc/Hsp70 Proteine die Genauigkeit der Zytokin-induzierten p65 Umlagerung kontrollieren. Die pharmakologische Inhibition der Hsp/Hsc70 Proteine resultierte in veränderter p65 Ubiquitinierung und Stabilität. Ebenso führte die Hsp/Hsc70 Inhibition zu einer verringerten p65-induzierten Aktivität eines Reportergens, sodass die Chaperon Aktivität einen wichtigen Beitrag für die Aktivität des p65 Proteins im Zellkern hat. Es ist wahrscheinlich, dass unterschiedliche p65 Konformationen das Repertoire an möglichen p65 Modifikationen und Protein/Protein Interaktionen stark erhöhen. Weitere Experimente zeigten, dass die Zytokin-induzierte p65 Umlagerung unabhängig von der DNA-Bindungsfähigkeit von p65 ist. Im zweiten Teil dieser Arbeit wurde die Wichtigkeit der DNA-Bindung für die Funktionen des p65 Proteins untersucht. Dazu wurden p65 knockout Zellen mit dem Wildtyp Protein sowie mit weiteren p65 Mutanten stabil rekonstituiert. Eine Mutante war DNA-Bindungsdefekt, währen die andere Mutante zusätzlich im Kerntranslokationssignal mutiert war. Die Analyse der TNF-induzierten Expression einiger NF-kB Zielgene zeigte, dass einige Gene trotz defekter p65 DNA-Bindung noch induzierbar exprimiert werden konnten. Dieses Verhalten ist wahrscheinlich auf kompensatorische Mechanismen wie beispielsweise eine Promoter-Rekrutierung via Protein/Protein Wechselwirkungen zurückzuführen. Die differentiell rekonstituierten Zellen werden in zukünftigen Studien wichtige Informationen über DNA-Bindungs-unabhängige Funktionen des p65 Proteins liefern können.
Regulation von NF-kappaBeta p65 durch Phosphorylierung, Chaperone und p65 DNA-Bindung
Keywords: NF-kappaBeta; p65; conformation; posttranslational modifications; chaperones; DNA binding; ddc:500